An Evaluation of the Effects of Formal Nutrition Education on Online Nutrition Information Retrieval among College Students. Issue 4 (1st October 2016) - Hayes, Logan; Bhochhibhoya, Amir; Cheney, Marshall; Larson, Daniel; Branscum, Paul
ABSTRACT: Few studies have examined online nutrition-health information seeking practices by college students using observational methods. The purpose of this study was to describe how college students search for health facts and credible recommendations related to nutrition, and to examine differences in information searching practices between students who have completed or not completed a formal introductory nutrition course. Undergraduate students ( n  = 48) were given three nutrition fact scenarios and three nutrition recommendation scenarios and used the Internet to find solutions. Observations were recorded using video and audio recording software (Camtasia). Nutrition students had higher nutrition knowledge ( p  < .001) and reported significantly higher satisfaction with their overall performance ( p  < .035) compared to nonnutrition students. Overall, students with nutrition education were able to recognized reputable websites as sources, more so that students without nutrition education. Public health educators can use the information gained from this study to develop interventions that help young adults search for credible and accurate nutrition information online.